Teachers’ Inclusive Education Practices and Their Attitudes Toward Social Justice in the Classroom - Shao, Jin (Pacific International Journal, 2025)
This study examines the relationship between teachers’ self-assessed inclusive education practices and their attitudes toward social justice in the classroom. Conducted at Sanhe Yanjiao Enoch Experimental School in China, the research employed a descriptive-comparative-correlational design with 81 teacher respondents. Data were collected through a validated researcher-made questionnaire assessing demographic profiles, inclusive education practices , and social justice attitudes . Results indicated that teachers generally demonstrated positive self-assessments of both inclusive education practices and social justice attitudes, with strong agreement on principles of equity and diversity. However, areas for improvement were identified, including sustained professional development in understanding diverse learner needs and implementing culturally responsive strategies. Statistical analysis revealed no significant differences in self-assessed inclusive education practices or social justice attitudes based on demographic variables such as sex, educational attainment, length of service, or seminar attendance. A significant positive correlation was found between teachers’ inclusive education practices and their social justice attitudes, particularly in valuing diversity, fostering student engagement, and promoting equity. The findings underscore the importance of integrating social justice frameworks with inclusive education training to enhance teachers’ capacity to create equitable and inclusive learning environments. Recommendations include targeted professional development programs, reflective practices, and institutional support to strengthen teachers’ ability to address diverse learner needs through a social justice lens.